Outcomes of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for peritoneal mesothelioma and predictors of survival. (4th July 2018) - Gilani, Syeda Nadia Shah; Mehta, Akash; Garcia-Fadrique, Alfonso; Rowaiye, Babatunde; Jenei, Veronika; Dayal, Sanjeev; Chandrakumaran, Kandiah; Carr, Norman; Mohamed, Faheez; Cecil, Tom; Moran, Brendan
Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) benefits selected patients with peritoneal mesothelioma. We present the outcomes of this treatment strategy in a UK peritoneal malignancy national referral centre. Methods: Observational retrospective analysis of data prospectively collected in a dedicated peritoneal malignancy database between March 1998 and January 2016. Results: Of 1586 patients treated for peritoneal malignancy, 76 (4.8%) underwent surgery for peritoneal mesothelioma. Median age was 49 years (range 21–73 years). 34 patients (45%) were female. Of the 76 patients, 39 (51%) had low grade histological subtypes (mostly multicystic mesothelioma), and 37 (49%) had diffuse malignant peritoneal mesothelioma (DMPM; mostly epithelioid mesothelioma). Complete cytoreduction was achieved in 52 patients (68%) and maximal tumour debulking (MTD) was performed in 20 patients (26%); the remaining 4 patients (5%) underwent a laparotomy with biopsy only. HIPEC was administered in 67 patients (88%). Median overall (OS) and disease-free survival (DFS) after CRS was 97.8 (80.2–115.4) and 58.8 (47.4–70.3) months, respectively. After complete cytoreduction, 100% overall survival was observed amongst patients with low-grade disease. Ki-67 proliferation index was significantly associated with survival outcomes after complete cytoreduction for DMPM and was an independent predictor of decreased survival. Conclusion: With adequate patient selection (guided by histological classification and Ki-67 proliferation index) and complete cytoreduction with HIPEC, satisfactory outcomes can be achieved in selected patients with peritoneal mesothelioma.